Fabrication of maxillary single complete denture in a patient with deranged mandibular occlusal plane: A case report - Kam Wah Foong; Pravinkumar G. Patil (Elsevier, 2019)
Construction of a single complete denture (SCD) is a challenging clinical situation especially when the opposing natural dentition is not in a normal plane of occlusion. Mal-aligned, tilted or supra-erupted teeth in the opposing arch are some of the problems that should be corrected to achieve a balanced occlusion in patients who require SCD. Achieving harmonious occlusal plane is a primary objective of any restorative procedure to facilitate natural mandibular movements and ease of mastication. Establishment of normal occlusal plane in opposite arch is pre-requisite to maintain the stability of the SCD. This clinical report describes restoration of mandibular teeth (with severe attrition and deranged occlusion) by establishing normal plane of occlusion with the help of custom made occlusal plane template (OPT) followed by construction of a complete denture in maxillary arch. Keywords: Balanced occlusion, Composite restorations, Mastication, Occlusal plane, Single complete denture